2021
DOI: 10.3390/molecules26051260
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Phase Change Materials (PCM) Used for Solar Process Heat Applications

Abstract: The high intermittency of solar energy is still a challenge yet to be overcome. The use of thermal storage has proven to be a good option, with phase change materials (PCM) as very promising candidates. Nevertheless, PCM compounds have typically poor thermal conductivity, reducing their attractiveness for commercial uses. This paper demonstrates the viability of increasing the PCM effective thermal conductivity to industrial required values (around 4 W/m·K) by using metal wool infiltrated into the resin under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In [11], the authors have reported that metal wool can be used as a low-cost additive to increase the thermal conductivity of thermal storage PCMs. It was established that to achieve an increase in the effective thermal conductivity of composite PCM (epoxy resin of 90 vol.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11], the authors have reported that metal wool can be used as a low-cost additive to increase the thermal conductivity of thermal storage PCMs. It was established that to achieve an increase in the effective thermal conductivity of composite PCM (epoxy resin of 90 vol.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Some researches aimed to eliminate this problem and focused on finding ways to increase the thermal conductivity of existing thermal storage PCMs. Several approaches are considered: installing metal fins in TES devices [3] or capsules with thermal storage PCM [4], adding nanoparticles [5] to thermal storage PCM, including nanoparticles of metal oxide [6], carbon nanotubes and nanofibers [7][8][9], introduction of thermal storage PCMs into highly thermally conductive structures made from expanded graphite [9] or metal matrixes [10], adding highly thermally conductive metal wool [3,11,12], etc. Thus, the investigation aimed at increasing the thermal conductivity of thermal storage PCMs is currently relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Typical values of density of energy storage are in the order of 50 kWh/m 3 (0.02 kWh/kg). A second way is to rely on latent heat storage, i.e., on the enthalpy variation that accompanies, at a conceptually constant temperature, the phase change (solid–solid, solid–liquid, liquid–gas) of a given substance. Here, the endothermal phase change (driven by solar energy) is the charging stage, and the reverse exothermal one is the discharging stage.…”
Section: Overviewmentioning
confidence: 99%
“…There are different techniques which have been used to improve the heat transfer characteristics of the energy storage systems. These techniques include microencapsulation of PCM [ 1 ], adding nanoparticles [ 2 , 3 , 4 ], absorption of phase change materials in metal foam [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and insertion of fins [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%